Edukasi Metode Kontrasepsi Jangka Panjang di Puskesmas Pakuan Baru Kota Jambi - Ria Febrina (Jurnal Abdimas Kesehatan (JAK), 2021)
Indonesia is currently experiencing population problems, one of which is the population explosion or the continued significant increase in population volume in Indonesia, on the other hand the population distribution is uneven. Based on a population survey in 2010, Indonesia's population was 237.6 million with a population growth rate of around 1.49%. If the government does not succeed in reducing population growth, it is predicted that Indonesia's population in 2060 will reach 475 million - 500 million. One of the government's efforts to control the rate of population growth is through the implementation of the Family Planning (KB) program for Fertile Age Couples (PUS) with the use of contraception. The use of long-term contraceptive methods (MKJP) is still very low, the total of active family planning participants, only 17.45% of them use MKJP KB. Meanwhile, 81.23% were non use of long-term contraceptive methods users and 1.32% used traditional family planning. Public health center of Pakuan Baru in 2018 there were no active family planning participants who used long-term contraceptive methods.Therefore, it is necessary to provide education to increase knowledge of fertile age woman (PUS) about MKJP and increase the coverage of long-term contraceptive methods. Implementation time in Nopember2019-Januari 2020. The targets are women of childbearing age at the public health center of Pakuan Baru. Community service methods include survey and lecture approaches. The results obtained were that fertile age woman was able to understand about long-term contraceptive methods and willing to use long-term contraceptive methods. It is recommended that the public health center maintain the extension program related to long-term contraceptive methods that has been provided.